Challenges in managing occupational safety and health for SMEs in the construction industry: A review - Naz Edayu, Mat Nawi; Ezrin Hani, Sukadarin (2022)
The construction industry is known as one of the largest industries in Malaysia. In the construction industry, different parties include clients, consultants and contractors that perform various roles in completing the project. It is believed that small-grade contractors are widely exposed to the highest rate of accidents or risks compared to medium and large-grade contractors (G5- G7) in the construction industry. Therefore, to clarify the issues on the safety matter, this paper has discussed the problem faced by small-grade contractors that influence the implementation of safety practices on site. It is hoped issues that arose will be caught by other parties to further work on improving construction safety as a whole.